Uslūb al-Bayān fī Syiʽr al-Khamriyāt li Abī Nuwās: Dirāsah Balāgiyah - Silviana, Yolanda (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2021)
Khamr has been the goal of shi'ir since Jahiliyah era. In Abbasid Period, the majority of the people came from ethical people, lived in luxury and extravagance. So, at this time there were many witty poets, sprees, and drinking khamr hobby. One of the poets who is famous for his Syi'ir Khumriyat is Abu Nuwas. Therefore, the author is interested in examining the beauty of the uslub language style on Syi'ir Khumriyat. The formulation of the problem is studying the themes of Abu Nuwas’s syi'ir stanza and how is Abu Nuwas describes the beauty of khamr in his syi'ir in terms of Bayan, and why is Syi'ir Khumriyat’s Abu Nuwas looks beautiful. In this study, it can be concluded that the themes of Syi'ir Khumriyat’s Abu Nuwas stanzas are numerous. However, the author only quotes part of it. The Uslub used is Uslub Adaby containing Bayan elements which include Tasybih, Majaz Lughawi bil Isti'arah makniyah wa tashrihiyah wa tamtsiliyah, Majaz Mursal, Majaz 'Aqli, and Kinayah. Likewise, the depiction of Syi'ir Khumriyat Abu Nuwas has a strong imagination, amazing parables, and has figurative language in the texts, so it looks beautiful.